Eksplorasi Tipe Kepribadian Big Five Personality Traits Dan Pengaruhnya Terhadap Prestasi Akademik - Asina Christina Rosito (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
The aim of this study were to explore the type of personality based on Big Five Personality Traits model, to explore the academic achievement, and to investigate the effect of personality on academic achievement in college students. The participants are 321 students at University of HKBP Nommensen in 2015-2016 academic year. The instrument used for assessing the personality was the Big Five Personality Scale (includes dimensions neuroticsm, extraversion, conscientiousness, agreeableness, dan openness). Based on the descriptive analysis, it was found that most of the participants are classified in neuroticsm type. Related with the academic achievement, higher GPA was dominated by female students (GPA ≥2.75). Based on the regression analysis, it was found that personality effect the academic achievement significantly (R= 0,26; R2 = 6,9 %; F= 4,69; p-value <0,001). Based on the advance analysis of each dimension’s contribution for academic achievement, it was found that neuroticsm, extraversion, conscienstiousness are significantly effected academic achievement.